The Myth of the Politics of Regret. (January 2015) - Toth, Mano
This article argues for the need to think about the politics of regret more critically, within academia and beyond. The politics of regret here refers to the process through which the representation of past events comes to be dominated by apologetic voices in the public discourse. A brief overview of the most prominent previous attempts to make sense of the phenomenon shows why it is vital to strengthen the critical perspective on the issue. I assume that, in practice, the politics of regret almost always makes use of simplified representations of historical events that constitute images of the self and of wider society; as such, it should be properly understood as mythical. For this reason, I argue that the critical (scholarly and social) approach to the politics of regret should be based on a more general ethical framework with regard to myths that simultaneously acknowledges the right to existence of all interpretations of the past (including political regret) and challenges the exclusionary characteristics of mythologies.